Exercise protects vascular function by countering senescent cells in older adults - Meng, Jinqi; Geng, Qi; Jin, Sheng; Teng, Xu; Xiao, Lin; Wu, Yuming; Tian, Danyang (Frontiers in Physiology, 2023)
Blood vessels are key conduits for the transport of blood and circulating factors. Abnormalities in blood vessels promote cardiovascular disease (CVD), which has become the most common disease as human lifespans extend. Aging itself is not pathogenic; however, the decline of physiological and biological function owing to aging has been linked to CVD. Although aging is a complex phenomenon that has not been comprehensively investigated, there is accumulating evidence that cellular senescence aggravates various pathological changes associated with aging. Emerging evidence shows that approaches that suppress or eliminate cellular senescence preserve vascular function in aging-related CVD. However, most pharmacological therapies for treating age-related CVD are inefficient. Therefore, effective approaches to treat CVD are urgently required. The benefits of exercise for the cardiovascular system have been well documented in basic research and clinical studies; however, the mechanisms and optimal frequency of exercise for promoting cardiovascular health remain unknown. Accordingly, in this review, we have discussed the changes in senescent endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) that occur in the progress of CVD and the roles of physical activity in CVD prevention and treatment.